2014
DOI: 10.5433/1679-0359.2014v35n5p2485
|View full text |Cite
|
Sign up to set email alerts
|

Milk contamination by organophosphorus and carbamate residues present in water and animal feedstuff

Abstract: ResumoNo Brasil, as exigências legais quanto ao controle de qualidade do leite cru se restringem à análise microbiológica, físico-química e à pesquisa de antimicrobianos. Contudo, os agrotóxicos podem ser detectados no leite após a exposição dos animais em lactação a esses agentes. O objetivo deste trabalho foi pesquisar a presença de organofosforados (OF) e carbamatos (CB) em amostras de água e de alimentos fornecidos às vacas leiteiras e também no leite produzido por esses animais. Todas as amostras foram an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
(17 reference statements)
0
4
0
Order By: Relevance
“…CBs were not present in milk however, they were present in feedstuff and water samples. Same ingredient was noticed in 3 dairy farms [35].…”
Section: Status Of Pesticide Residues In Milk and Milk Productsmentioning
confidence: 83%
“…CBs were not present in milk however, they were present in feedstuff and water samples. Same ingredient was noticed in 3 dairy farms [35].…”
Section: Status Of Pesticide Residues In Milk and Milk Productsmentioning
confidence: 83%
“…The organophosphate diazinon is used to control cattle ticks in various regions. Organophosphate residues have been detected in raw milk (FAGNANI et al, 2011;JARDIM et al, 2018;NERO et al, 2007;SILVA et al, 2014). Organophosphate residues detected in raw milk are similar to those detected in animal feed (FAGNANI et al, 2011;SILVA et al, 2014).…”
Section: Acaricide Control Of R Microplus and Food Contamination Conc...mentioning
confidence: 53%
“…Organophosphate residues have been detected in raw milk (FAGNANI et al, 2011;JARDIM et al, 2018;NERO et al, 2007;SILVA et al, 2014). Organophosphate residues detected in raw milk are similar to those detected in animal feed (FAGNANI et al, 2011;SILVA et al, 2014). It has been suggested that the levels of organophosphate contamination of milk can be explained by the animal feed, in which organophosphates are present, since they are widely used in crops used to produce animal feed (FAGNANI et al, 2011).…”
Section: Acaricide Control Of R Microplus and Food Contamination Conc...mentioning
confidence: 79%
“…Da Silva et al [13] were investigated organochlorine pesticides in Brazil in feedstuff, water and dairy milk. Total 30 milk samples were analyzed out of which 17% samples were contaminated with OPPS.…”
Section: Discussionmentioning
confidence: 99%